Nontraumatic Spontaneous Bilateral Intracerebral Hemorrhage: A Rare Case Serial - Rosalina Pradana Ayu; Raden Andi Ario Tedjo; Siti Roisya Aga Maydiana (Magna Neurologica, 2025)
Background: Nontraumatic spontaneous bilateral intracerebral bleeding is infrequent, with only 30-40 cases reported worldwide. Hypertension is the leading cause due to the formation of microaneurysms at the lenticulostriate arteries. Treatment follows current intracerebral hemorrhage guidelines, focusing on supportive care and early blood pressure management. This case report aims to further understand nontraumatic spontaneous bilateral intracerebral hemorrhage. Case: We report two cases of nontraumatic bilateral spontaneous intracerebral hemorrhage with similar etiologies. The first case involved a 34-year-old male with weakness in the right extremities, slurred speech, and high blood pressure (213/138 mmHg). The second case involved a 65-year-old woman with weakness in the left extremities, slurred speech, and high blood pressure (175/95 mmHg). Both patients had bilateral hemorrhages in different areas of the brain. They were treated according to management guidelines for intracerebral hemorrhage and showed improvement. Discussion: Nontraumatic spontaneous bilateral intracerebral bleeding is often caused by hypertension. CT angiography is a vital test for identifying vascular abnormalities. Treatment involves reducing risk factors for complications and controlling blood pressure. Typically, management of this condition is conservative, and unfavorable outcomes are common. However, these patients showed improvement. Conclusion: Conservative management, supportive care, and early blood pressure management for nontraumatic spontaneous bilateral intracerebral hemorrhage patients can cause improvement in the patient's condition.